Perancangan Aplikasi E-Commerce Hasil Pertanian Desa Kedungrejo Berbasis Android: Designing an Android-Based Agricultural Products E-Commerce Application for Kedungrejo Village - Aisyah, Firda; Jatmika, sunu (JURNAL SISTEM KOMPUTER ASIA, 2023)
With the development of nowadays technology, this application is made to make it easier for buyers to order the desired vegetables from anywhere and anytime very easily. This e-commerce application uses the Android-based Flutter framework for the needs of buying and selling vegetables between sellers at the Kedungrejo Vegetable Market and prospective buyers from all over Malang. In this test, the application is testing by testing users and admin’s application to find out whether the application is running well or not.